A parametric analysis of the aerodynamic characteristics of volleyballs in turbulent flow - Thomas, H. J. (2012)
A wind tunnel experiment was conducted to compare the flight path characteristics and drag of current models of volleyballs. An open circuit low speed wind tunnel was primarily used to gather lift and drag data on multiple models of volleyballs in super-critical Reynolds number flows. The models tested were the Baden VX5E-01, Baden VX450C-230, Baden VX450-02, Mikasa MVA200, and Molten V5M5000. Analysis was conducted to determine the relationship between cavity dimensions on the balls and the lift and drag characteristics of the balls. Conditions were based on indoor volleyball conditions set by the International Federation of Volleyball (FIVB) with Reynolds numbers ranging from 2x105 to 4.3x105. Recommendations were provided for future designs of volleyballs to improve aerodynamic performance.